Diabulimia in Adult Patients with Type 1 Diabetes - Review of Literature - Piotrowski, Karol; Jerczak, Małgorzata; Pluszyński, Tomasz; Padula, Natalia; Piórkowska, Iga; Polewka, Mikołaj; Polańska, Aleksandra; Paczosa, Kacper; Przybył, Filip (Quality in Sport, 2026)
Background: “Diabulimia” refers to intentional insulin restriction/omission in type 1 diabetes (T1D) to influence weight. It remains unrecognized in formal classification systems, complicating clinical coding. This behavior is a dangerous form of disordered eating linked to metabolic decompensation (recurrent ketoacidosis) and poorer prognosis. Aim: This article synthesizes evidence on diabulimia in adults with T1D, focusing on epidemiology, etiology, diagnostics, clinical presentation, complications, treatment, and prevention. Material and methods: A narrative synthesis was conducted using peer-reviewed reviews, observational studies, and case reports addressing: (I) insulin restriction as disordered eating, (II) acute metabolic crises (DKA), (III) chronic complications, and (IV) diagnostic challenges in adults (adult-onset T1D, LADA, secondary diabetes). Results: Diabulimia is characterized by weight-motivated insulin restriction and remains underdiagnosed due to a lack of formal criteria and overlap with diabetes distress. Evidence indicates a clinically meaningful prevalence of disordered eating in T1D adults, though data for older groups are limited. Reported outcomes include recurrent DKA and a rapid pathway to microvascular and neuropathic complications driven by chronic hyperglycemia. Conclusion: Diabulimia in adults is a high-risk condition at the interface of endocrinology and mental health. It requires interdisciplinary management, proactive detection of poor metabolic control, exclusion of diagnostic mimics (LADA/secondary diabetes), and combined psychological and diabetes-care interventions.